DIFFERENT APPROACHES OF LINGUISTS TO EMOTIONS (Web of Teachers: Inderscience Research, 2025)
This thesis delves into the complex relationship between feelings and emotions, examining how these concepts are used and interpreted across different disciplines. The author critiques the common tendency to view emotions as more objective and therefore more amenable to scientific study than feelings, highlighting the “flight from subjectivity” that often characterizes this approach. The problematic nature of the term “emotion” itself is explored, emphasizing its multifaceted nature encompassing not only physiological changes but also feelings, thoughts, and behaviors. The influence of language on our understanding of these concepts is also addressed, particularly how the English word “emotion” conflates feeling, thinking, and bodily experience.